(Liquid + liquid) equilibria for (benzene + cyclohexane + dimethyl sulfoxide) system at T = (298.15 or 303.15) K: Experimental data and correlation. (May 2015) - Yang, Xiaoguang; Zhang, Xiqiang; Dong, Hongxing; Yue, Guojun; Liu, Jinsong
Graphical abstract: The selectivity of DMSO, is usually high. At 25 °C and atmospheric pressure, the selectivity coefficient can reach beyond 14, which means that DMSO can compete with some ionic liquids for extracting benzene from cyclohexane. So, DMSO has large potential to separate benzene from cyclohexane as a new extractant. Highlights: The highest selectivity coefficient is beyond 14 of DMSO at T = (298.15 or 303.15) K. The data's reliability is approved by the correlation of Othmer–Tobias equation. NRTL model is in good agreement with the experimental data. Abstract: (Liquid + liquid) equilibrium (LLE) data were measured experimentally at T = (298.15 or 303.15) K and atmospheric pressure for the (benzene + cyclohexane + dimethyl sulfone (DMSO)) system. The Othmer–Tobias equation was applied to verify the reliability of the data. Based on the data, the selectivity of DMSO was estimated and compared with that of ionic liquids. The highest selectivity coefficient of DMSO can reach beyond 14, which means it is able to compete with some ionic liquids and it would be a good extractant to separate benzene from cyclohexane. At the same time, the NRTL model was used to correlate the data and the results show that the model agrees on the experimental data very well.